Preparation method of light-transmitting ceramic tile of strontium-aluminum-silicon system and light-transmitting ceramic tile

By adjusting the raw material formula of the strontium aluminum-silicon system, strontium feldspar with a refractive index close to that of calcium feldspar and quartz, the problem of low light transmittance in existing ceramic tiles is solved, and high light transmittance and widening of application scope is achieved.

CN119191827AActive Publication Date: 2024-12-27CHONGQING WONDERFUL CERAMICS CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411343966.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing transparent ceramics have low light transmittance and cannot achieve high light transmittance effects. This is mainly due to the large difference in refractive index of mullite produced by kaolin calcination, which reduces the transparency of the ceramics.

Method used

The method of producing translucent ceramic tiles using strontium aluminum-silicon system is used to adjust the formula ratios of kaolin, strontium carbonate, potassium feldspar, low-temperature fuse and quartz to form strontium feldspar with refractive index close to calcium feldspar and quartz, avoiding duo The generation of stones can improve the light transmittance of ceramic tiles.

Benefits of technology

It achieves high light transmittance of ceramic tiles, broadens the firing temperature range, reduces the risks of deformation and foaming, is suitable for ceramic tiles of various specifications, and improves the density and transparency of the blank.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191827A_ABST
    Figure CN119191827A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a light-transmitting ceramic tile of a strontium-aluminum-silicon system and the light-transmitting ceramic tile. The preparation method of the light-transmitting ceramic tile of the strontium-aluminum-silicon system comprises the following steps: selecting a target raw material formula in a pre-constructed raw material formula table according to the specification of the light-transmitting ceramic tile to be prepared; preparing the light-transmitting ceramic tile according to the target raw material formula; wherein the raw material formula table comprises a plurality of raw material formulas, the raw materials in each raw material formula comprise kaolin, strontium carbonate, potassium feldspar, low-temperature frit, strontium feldspar and / or quartz, and the kaolin in each raw material formula accounts for different weight percentages. In the calcining process of the kaolin, strontium feldspar with the refractive index extremely close to that of anorthite is formed by the kaolin and strontium carbonate, and strontium ice feldspar with the refractive index closer to that of quartz can be formed by the strontium feldspar and potassium-sodium feldspar at a high temperature, so that mullite does not exist in a ceramic green brick any more, and the light transmittance of the green body is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic production, and in particular to a method for preparing a strontium aluminum silicon system light-transmitting ceramic tile and the light-transmitting ceramic tile. Background Art

[0002] Ceramics are fine polycrystalline sintered bodies, mainly composed of grains, grain boundaries, glass phase, pores, impurities, etc. Ceramics appear opaque due to the reflection, refraction and scattering of light. To make ceramics as transparent as glass, the prerequisite is to allow light to pass through.

[0003] Kaolin, feldspar, and quartz are the main raw materials for traditional ceramic bodies. Kaolin is calcined at high temperatures to eventually form mullite, and the refractive index of mullite is 1.63-1.69, which is greater than 0.1 compared to the refractive index of 1.5 of the glass formed after calcination of potassium-sodium feldspar. The more mullite there is in the body, the higher the degree of devitrification of the body. In other words, the higher the kaolin content in the body formula, the more mullite crystal phases will be generated after high-temperature calcination, and the higher the degree of devitrification of the body. This is one of the fundamental reasons for the devitrification of traditional ceramic bodies. Therefore, existing transparent ceramics can only achieve a lower transmittance.

[0004] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a strontium aluminum silicon system translucent ceramic tile and a translucent ceramic tile in view of the above-mentioned defects of the prior art, aiming to solve the problem that transparent ceramics in the prior art can only achieve a low light transmittance.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0007] The first embodiment of the present application provides a method for preparing a strontium aluminum silicon system light-transmitting ceramic tile, wherein the method comprises:

[0008] Selecting a target raw material formula from a pre-constructed raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared;

[0009] preparing light-transmitting ceramic tiles according to the target raw material formula;

[0010] The raw material formula table includes several raw material formulas, and the raw materials in each raw material formula include: kaolin, strontium carbonate, potassium feldspar, low-temperature frit, strontium feldspar and / or quartz, and the weight percentage of kaolin in each raw material formula is different.

[0011] In one embodiment of the present application, the total weight percentage of potassium feldspar and low-temperature melt in each raw material formula is 25-35%.

[0012] In one embodiment of the present application, the chemical components of the low-temperature frit include, by weight percentage:

[0013] SiO2 70-72%, Al2O3 1-3%, Fe2O3 0-0.2%, TiO2 0-0.05%, CaO 5-10%, MgO 3-5%, K2O 0-1.5%, Na2O 8-16%, and the rest is loss on ignition;

[0014] Alternatively, the chemical components of the low-temperature frit include, by weight percentage:

[0015] SiO2 50-60%, Al2O3 2-3%, Fe2O3 0-0.2%, TiO2 0-0.05%, CaO 0-0.5%, MgO 0-0.5%, SrO 8-12%, K2O 0-5%, Na2O 8-16%, and the rest is loss on ignition;

[0016] Alternatively, the chemical components of the low-temperature frit include, by weight percentage:

[0017] SiO2 50~60%, Al2O3 2~3%, Fe2O3 0~0.2%, TiO2 0~0.05%, CaO 0~0.5%, MgO 0~0.5%, SrO 8~12%, K2O 0~5%, Na2O 8~16%, MoO3 0~2%, and the rest is loss on ignition.

[0018] In one embodiment of the present application, the steps of preparing strontium feldspar include:

[0019] Kaolin, strontium carbonate and potassium feldspar are prepared according to a predetermined raw material formula, and the sintering temperature is 1450℃~1500℃.

[0020] In one embodiment of the present application, the chemical components of the strontium feldspar include, by weight percentage:

[0021] SiO2 26~31%, Al2O3 20~21%, Fe2O3 0.15~0.25%, TiO2 0~0.05%, CaO0~0.2%, MgO 0~0.2%, SrO 30~35%, K2O 0~1.4%, Na2O 0~0.5%, and the rest is loss on ignition.

[0022] In one embodiment of the present application, the raw material formula in the raw material formula table includes, by weight percentage:

[0023] Kaolin 20%, strontium carbonate 11-13%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 32-44%;

[0024] Kaolin 25%, strontium carbonate 14-16%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 24-36%;

[0025] Kaolin 30%, strontium carbonate 17-19%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 16-28%;

[0026] Kaolin 35%, strontium carbonate 20-22%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 8-20%;

[0027] Kaolin 40%, strontium carbonate 23-25%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 0-12%;

[0028] Kaolin 45%, strontium carbonate 26-28%, potassium feldspar + low-temperature frit 20-30%, strontium feldspar and / or quartz 0-9%.

[0029] In one embodiment of the present application, before selecting a target raw material formula in a pre-constructed raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared, the method further includes:

[0030] Establish the correspondence between specifications and the weight percentage of kaolin.

[0031] In one embodiment of the present application, a target raw material formula is selected from a pre-constructed raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared, including:

[0032] Find the corresponding relationship according to the specifications of the light-transmitting ceramic tile to be prepared, and obtain the weight percentage of the target kaolin;

[0033] Select the target raw material formula corresponding to the weight percentage of the target kaolin in the pre-constructed raw material formula table.

[0034] In one embodiment of the present application, a light-transmitting ceramic tile is prepared according to the target raw material formula, including:

[0035] Mix the raw materials according to the target raw material formula, add water and additives to perform wet ball milling;

[0036] The ball-milled raw material is sieved to remove iron and spray-dried to obtain a powder;

[0037] Pressing the powder into a green body, drying the green body, and spraying water on the surface of the dried green body;

[0038] Applying base glaze and top glaze to the green body after water spraying, and firing the glazed green body in a kiln at an ambient temperature of 1130°C to 1200°C to obtain a light-transmitting ceramic tile;

[0039] Among them, the ring temperature is inversely proportional to the amount of low-temperature melt added.

[0040] The present application also provides a light-transmitting ceramic tile, wherein the light-transmitting ceramic tile is prepared by the light-transmitting ceramic tile preparation method of the strontium aluminum silicon system as described above.

[0041] The present invention discloses a method for preparing a light-transmitting ceramic tile of a strontium aluminum silicon system and a light-transmitting ceramic tile. The method for preparing a light-transmitting ceramic tile of a strontium aluminum silicon system comprises: selecting a target raw material formula in a pre-constructed raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared; preparing the light-transmitting ceramic tile according to the target raw material formula; wherein the raw material formula table comprises several raw material formulas, and the raw materials in each raw material formula all comprise: kaolin, strontium carbonate, potassium feldspar, low-temperature frit, strontium feldspar and / or quartz, and the weight percentage of kaolin in each raw material formula is different. During the calcination process, the kaolin in the present invention forms strontium feldspar with strontium carbonate, which has a refractive index very close to that of calcium feldspar, and strontium feldspar can form strontium cryolite with potassium sodium feldspar at high temperature, which has a refractive index closer to that of quartz. In this way, mullite no longer exists in the ceramic tile blank, thereby improving the light transmittance of the blank. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a flow chart of a preferred embodiment of a method for preparing a light-transmitting ceramic tile of a strontium aluminum silicon system in the present invention.

[0043] Figure 2 This is a laser particle size analysis diagram of the blank fineness of a preferred embodiment of a method for preparing a strontium aluminum silicon system translucent ceramic tile in the present invention.

[0044] Figure 3 It is a light transmission effect diagram of the light-transmitting ceramic tile prepared by the present invention. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0046] The light transmittance of ceramics is mainly affected by the following factors:

[0047] 1. Porosity. The pores and holes in the grains and the glass phase at the grain boundaries constitute the second phase: the gas phase. The refractive index of the gas phase is very low, about 1. The refractive index difference with the main crystal phase in the ceramic is often large, and the number is extremely large. Therefore, the existence of pores will greatly reduce the transparency of the material. When the pore volume accounts for 3%, the transmittance is 0.01%; when the pore volume accounts for 0.3%, the transmittance is 10%. Therefore, transparent ceramics must increase density and reduce porosity, and the density is usually greater than 99.9%.

[0048] 2. Impurity phase. Since the refractive index of the impurity phase is different from that of the main crystal phase, light scattering will occur at the phase boundary, reducing the transmittance of the ceramic. The light transmittance of ceramics depends largely on the difference in the refractive index of its constituent phases. The greater the difference and the more impurity phases in the ceramic, the lower its light transmittance. Therefore, generally transparent ceramics use high-purity raw materials to ensure the purity of their phases.

[0049] 3. Crystal structure characteristics. The grain orientation of polycrystalline ceramic materials is chaotic. Non-cubic crystals can only improve the light transmittance of ceramics when the grain orientation is the same. Disordered and chaotic grain arrangement will lead to reduced transparency. Cubic crystals have no anisotropy, and the difference in refractive index along the optical axis is zero, so they may have higher light transmittance.

[0050] 4. Grain size. When the grain size is equal to the wavelength of the incident light wave, the light will be scattered to the maximum. Therefore, to improve the transmittance of ceramics, the grain size of the material should be outside the wavelength range of the visible spectrum (0.4 to 0.8 microns). Either it is smaller than the wavelength of the light wave, that is, the grain size is less than 0.4 microns; or it is larger than the wavelength of the light wave, that is, the grain size is greater than 0.8 microns.

[0051] 5. Grain boundary. The grain boundary of transparent ceramics is clean, clear and very narrow. If there is a certain difference in refractive index between the grain boundary and the grain, it will affect the transmittance. Transparent ceramics require clean grain boundaries and no segregation of secondary phases.

[0052] 6. Surface roughness. The transmittance of transparent ceramics is restricted by the surface roughness. The greater the surface roughness of sintered ceramics, the lower its light transmittance.

[0053] Kaolin, feldspar, and quartz are the main raw materials for traditional ceramic bodies. Kaolin is calcined at high temperatures to eventually form mullite, and the refractive index of mullite is 1.63-1.69, which is much greater than 0.1 compared to the refractive index of 1.5 of the glass formed after calcination of potassium-sodium feldspar. The more mullite in the body, the higher the degree of devitrification of the body. In other words, the higher the kaolin content in the body formula, the more mullite crystal phases will be generated after high-temperature calcination, and the higher the degree of devitrification of the body. This is one of the fundamental reasons for the devitrification of traditional ceramic bodies.

[0054] Potassium-sodium feldspar is calcined at high temperature to form glass with a refractive index of 1.5, which is only 0.05 different from the refractive index of quartz 1.55. Therefore, by increasing the quartz content in the body, the transparency of the porcelain body will be greatly improved.

[0055] The second fundamental reason for the devitrification of traditional ceramic bodies is porosity. Low porosity is the key factor in increasing transparency.

[0056] There are four main ways to achieve light transmission in traditional ceramic bodies: 1. High-white potassium-based bodies; 2. High-quartz light-transmitting ceramic bodies; 3. Bone ash porcelain with calcium phosphate and bone ash; 4. Introducing CaO to generate calcium feldspar crystals with a refractive index difference of less than 0.1 with quartz. The formulas of many light-transmitting ceramic tile bodies in the current ceramic tile industry are representative, as shown in Table 1.

[0057] Table 1

[0058]

[0059]

[0060] Because the light transmittance of translucent ceramic tiles is not very high, the architectural ceramic tile industry calls translucent ceramic tiles according to different categories as translucent rock slabs, translucent ceramic tiles, translucent jade tiles, jade polished tiles, etc. At present, the translucent ceramic tile blanks disclosed by the ceramic tile industry are mostly based on calcium systems. Some can be put into production, while others have inherent defects in formula design and are difficult to put into industrial production.

[0061] In the past ceramic industry, calcium-based green bodies were only used for ceramic wall tiles, and rarely for porcelain green bodies. This is because CaO has the ability to increase the high-temperature viscosity of the glass phase at low temperatures, and greatly reduce the high-temperature viscosity of the glass phase at high temperatures. The "fast melting" and "short-lived" characteristics of CaO restrict its application in porcelain tile green bodies.

[0062] In a ceramic body with a high CaO content, the viscosity of the CaO-containing glass phase tends to be low, causing the ceramic body to be easily deformed and even produce serious defects such as foaming; the firing range of CaO-containing products is narrower than that of traditional bodies, which is also caused by the CaO-containing glass phase. This is the main problem of calcite, including calcium oxide-containing silicates (wollastonite, diopside) having an adverse effect on ceramic bodies.

[0063] In order to improve the light transmittance, the light-transmitting blank must have a very low porosity, thus becoming a porcelain blank. However, CaO in the porcelain blank easily causes the blank to deform or even foam. Therefore, the firing temperature range of the calcium-based light-transmitting blank is relatively narrow, and the production is relatively difficult, which is due to the inherent defects of its formula system design.

[0064] The embodiments of the present application can broaden the firing temperature range of the translucent ceramic body and solve the deformation and blistering of ceramic tiles; can meet the needs of various specifications of ceramic tiles, that is, according to the requirements of different specifications of products on the green body strength, the amount of kaolin added can be adjusted at will, and the transmittance is not affected; can meet different firing temperatures, that is, firing high-temperature and low-temperature frits, and adjusting the ratio of potassium feldspar to the low-temperature frit according to the firing temperature, and the transmittance of the body is not affected.

[0065] See also Figure 1 , Figure 1 The figure is a flow chart of the method for preparing the light-transmitting ceramic tile of the strontium aluminum silicon system in the present invention. Figure 1 As shown, the method for preparing the light-transmitting ceramic tile of the strontium aluminum silicon system described in the embodiment of the present invention comprises the following steps:

[0066] Step S100, selecting a target raw material formula from a pre-constructed raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared;

[0067] Step S200, preparing light-transmitting ceramic tiles according to the target raw material formula; wherein the raw material formula table includes several raw material formulas, and the raw materials in each raw material formula include: kaolin, strontium carbonate, potassium feldspar, low-temperature frit, strontium feldspar and / or quartz, and the weight percentage of kaolin in each raw material formula is different.

[0068] The formula of the light-transmitting ceramic tile in the embodiment of the present application includes three parts. The first part is the strontium feldspar raw material synthesis part, including kaolin and strontium carbonate.

[0069] Specifically, if the green strength of the ceramic body is not enough, cracks and fractures will occur during the production process, resulting in a decrease in the quality rate of production and an increase in costs. If the product specifications are large, the green strength requirements are high; if the product specifications are small, the green strength requirements are low. Depending on the product, the green strength requirements vary from 2 to 6 MPa, and the amount of kaolin in the body formula varies from 20 to 42wt%.

[0070] In ceramic green bodies, SrO has a wide melting range and is not fast-melting. After calcination, kaolin easily forms mullite with a high refractive index, which causes the green body to lose transparency. Kaolin is an indispensable and widely used raw material in green bodies, especially in rock slab products. If kaolin forms strontium feldspar with strontium carbonate during the calcination process, and strontium feldspar forms strontium cryolite with a refractive index closer to quartz with potassium-sodium feldspar at high temperatures, then mullite will no longer exist in the ceramic tile green body, thereby improving the light transmittance of the green body.

[0071] According to the equation of the reaction of kaolin with strontium carbonate at high temperature:

[0072] SrCO3+Al2O3·2SiO2·2H2O-900℃ and above→SrO·Al2O3·2SiO2+CO2↑+H2O;

[0073] As shown in Table 2, the mass ratio of kaolin to strontium carbonate has the following rules:

[0074] Table 2

[0075]

[0076] The above formula contains 20-30% kaolin, which is suitable for producing small-sized products such as those below 800*800mm, while 40% is suitable for the formula of rock slabs.

[0077] In the embodiments of the present application, the total weight percentage of potassium feldspar and low-temperature melt in each raw material formula is 25-35%.

[0078] The second part of the translucent ceramic tile formula of the embodiment of the present application is the green body sintering material part. Specifically, during the sintering process of the ceramic green body, liquid phase sintering is the main process and solid phase sintering is the auxiliary process. During the sintering process, the solid phase, liquid phase and pores coexist. During the sintering process, the low-temperature liquid phase fills the pores and consolidates the ceramic into a dense green body.

[0079] The strengthening effect of the liquid phase on sintering depends not only on the solubility between the liquid phase and the solid phase, the ability of the liquid phase to segregate at the sintering neck, and the high diffusivity of the solid phase in the liquid phase, but also on the ability of the liquid phase to wet the surface of the solid phase particles. Good wettability will facilitate the movement of the liquid phase in the pores and fill the pores in the green body.

[0080] The sintering materials that can meet the above conditions include potassium feldspar and low-temperature frit. Low-temperature frit has low surface tension and good solid-phase wettability, making it easier to fill the pores in the green body and make the green body dense. Keeping the total amount of potassium feldspar and low-temperature frit unchanged and increasing the amount of low-temperature frit, the sintering temperature can be reduced. Reducing the amount of low-temperature frit can increase the sintering temperature. The combination of the two can increase or decrease the green body sintering temperature within a certain range.

[0081] According to sintering theory and experiments, the total amount of potassium feldspar and low-temperature frit is 25-35wt%.

[0082] The embodiment of the present application can meet different firing temperatures, fire high-temperature and low-temperature frits, and adjust the ratio of potassium feldspar to the low-temperature frit according to the firing temperature, without affecting the light transmittance of the green body.

[0083] In one embodiment of the present application, the chemical components of the low-temperature frit include, by weight percentage:

[0084] SiO2 70-72%, Al2O3 1-3%, Fe2O3 0-0.2%, TiO2 0-0.05%, CaO 5-10%, MgO 3-5%, K2O 0-1.5%, Na2O 8-16%, and the rest is loss on ignition;

[0085] Alternatively, the chemical components of the low-temperature frit include, by weight percentage:

[0086] SiO2 50-60%, Al2O3 2-3%, Fe2O3 0-0.2%, TiO2 0-0.05%, CaO 0-0.5%, MgO 0-0.5%, SrO 8-12%, K2O 0-5%, Na2O 8-16%, and the rest is loss on ignition;

[0087] Alternatively, the chemical components of the low-temperature frit include, by weight percentage:

[0088] SiO2 50~60%, Al2O3 2~3%, Fe2O3 0~0.2%, TiO2 0~0.05%, CaO 0~0.5%, MgO 0~0.5%, SrO 8~12%, K2O 0~5%, Na2O 8~16%, MoO3 0~2%, and the rest is loss on ignition.

[0089] Specifically, the use of low temperature frit has the following schemes:

[0090] Solution 1: Use soda-lime-silica glass powder B01. The chemical components of soda-lime-silica glass powder B01 are calculated by weight percentage and include:

[0091] SiO2 70~72%, Al2O3 1~3%, Fe2O3 0~0.2%, TiO2 0~0.05%, CaO 5~10%, MgO 3~5%, K2O 0~1.5%, Na2O 8~16%, and the rest is loss on ignition.

[0092] Solution 2: Use low temperature frit K12. The chemical components of low temperature frit K12 are calculated by weight percentage, including:

[0093] SiO2 50~60%, Al2O3 2~3%, Fe2O3 0~0.2%, TiO2 0~0.05%, CaO 0~0.5%, MgO 0~0.5%, SrO 8~12%, K2O 0~5%, Na2O 8~16%, and the rest is loss on ignition.

[0094] Solution 3: Use low-temperature frit K12B sintered with molybdenum trioxide. The chemical components of low-temperature frit K12B, calculated by weight percentage, include:

[0095] SiO2 50~60%, Al2O3 2~3%, Fe2O3 0~0.2%, TiO2 0~0.05%, CaO 0~0.5%, MgO 0~0.5%, SrO 8~12%, K2O 0~5%, Na2O 8~16%, MoO3 0~2%, and the rest is loss on ignition.

[0096] The common characteristics of low-temperature frits are low aluminum content and high sodium content. Even molybdenum trioxide is added to the frit to make it have low surface tension at high temperature and good wettability, which makes it easier to promote liquid phase sintering of translucent ceramic tiles. It can be melted into the chemical composition of glass and can greatly reduce the surface tension. Among the four metal oxides of vanadium, chromium, molybdenum and tungsten, only molybdenum trioxide does not show color. Melting molybdenum oxide into the frit can reduce the surface tension of the frit, and it is the only choice for the body sintering material in the formula of translucent ceramic tiles.

[0097] Among the above low-temperature frits, the first choice is the low-temperature frit K12B containing molybdenum trioxide, followed by K12, and finally the soda-lime-silica glass powder B01. This is because the glass powder commonly used in the ceramic tile industry is purchased and recycled glass. Although it is cheap, its chemical composition will vary greatly from batch to batch.

[0098] In an embodiment of the present application, the preparation step of the strontium feldspar includes: preparing kaolin, strontium carbonate and potassium feldspar according to a predetermined raw material formula, and the sintering temperature is 1450°C to 1500°C.

[0099] The third part of the formula of the light-transmitting ceramic tile of the embodiment of the present application is the high-temperature filler part. In the formula where the amount of kaolin used is less than 25%, the total amount of kaolin and strontium carbonate is 31-41%, while the green body sintering material is 25-35%, and the sum of the two is 56-76%. Strontium feldspar (or strontium cryolite) or quartz is used to supplement the total amount to 100%, and potassium-sodium feldspar cannot be used. This is because potassium-sodium feldspar is easily fired into a glass phase at high temperature, plus the glass phase in the green body sintering material, there are too many glass phases in the formula, and there are low-temperature frits in the green body sintering material, which easily lead to defects such as bulging and black heart when the green body is at high temperature. However, this problem will not occur when using strontium feldspar or quartz that can only melt at a higher temperature. Furthermore, strontium feldspar (or strontium cryolite) can form a limited isomorphism with potassium-sodium feldspar at high temperature, and the refractive index is reduced, which is helpful for light transmission. The refractive index of quartz is also close to that of the glass in the body, so the loss of light transmittance is not significant.

[0100] Specifically, the formula of the frit of strontium feldspar (or strontium adularia) is: 50 parts of kaolin, 30 parts of strontium carbonate, and 0-10 parts of potassium feldspar. The firing temperature of the frit is 1450°C-1500°C.

[0101] In the embodiment of the present application, the chemical components of the strontium feldspar include, by weight percentage:

[0102] SiO2 26~31%, Al2O3 20~21%, Fe2O3 0.15~0.25%, TiO2 0~0.05%, CaO0~0.2%, MgO 0~0.2%, SrO 30~35%, K2O 0~1.4%, Na2O 0~0.5%, and the rest is loss on ignition.

[0103] In the examples of the present application, the raw material formula in the raw material formula table includes, by weight percentage:

[0104] Kaolin 20%, strontium carbonate 11-13%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 32-44%;

[0105] Kaolin 25%, strontium carbonate 14-16%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 24-36%;

[0106] Kaolin 30%, strontium carbonate 17-19%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 16-28%;

[0107] Kaolin 35%, strontium carbonate 20-22%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 8-20%;

[0108] Kaolin 40%, strontium carbonate 23-25%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 0-12%;

[0109] Kaolin 45%, strontium carbonate 26-28%, potassium feldspar + low-temperature frit 20-30%, strontium feldspar and / or quartz 0-9%.

[0110] The raw material formula is shown in Table 3:

[0111] Table 3

[0112]

[0113]

[0114] In the above formula, even for large-sized rock slabs, 40-42wt% kaolin is used, and with the addition of body reinforcing agents, the green body strength is sufficient. Therefore, a combination of 45wt% kaolin is basically not used.

[0115] In the formula, the Fe2O3 and TiO2 contents in kaolin are reduced, which has little effect on the transparency. However, the color of the body itself will be yellowish green (iron oxide coloring). The Fe2O3 content of kaolin in the formula is less than 0.4%, which barely meets the requirements, and less than 0.2% is a top grade. The Fe2O3 content in potassium feldspar, quartz, and frit must be less than 0.1%. TiO2 is extremely small. Kaolin, potassium feldspar, and quartz in the formula are all natural minerals, and strontium carbonate is industrial pure, and neither of them is listed as an ingredient.

[0116] In the embodiment of the present application, before step S100, the process further includes: establishing a corresponding relationship between the specification and the weight percentage of kaolin.

[0117] Due to the insufficient green strength of the ceramic body, cracks, fractures and other defects will occur during the production process, resulting in a decrease in the quality rate of production and an increase in costs. If the product specifications are large, the green strength requirements are high; if the product specifications are small, the green strength requirements are low. Depending on the product, the green strength requirements vary from 2 to 6 MPa, and the amount of kaolin in the body formula varies from 20 to 42wt%. Therefore, there is a certain correspondence between the specifications and the weight percentage of kaolin.

[0118] The embodiments of the present application can meet the needs of ceramic tiles of various specifications, thereby increasing the scope of application.

[0119] In the embodiment of the present application, the step S100 specifically includes:

[0120] Step S110, searching the corresponding relationship according to the specifications of the light-transmitting ceramic tile to be prepared, and obtaining the weight percentage of the target kaolin;

[0121] Step S120: Select a target raw material formula corresponding to the target kaolin weight percentage in the pre-constructed raw material formula table.

[0122] The embodiment of the present application can adjust the amount of kaolin added according to the requirements of green body strength of products of different specifications, and the light transmittance is not affected.

[0123] In the embodiment of the present application, the step S200 specifically includes:

[0124] Step S210, mixing the raw materials according to the target raw material formula, adding water and additives to perform wet ball milling;

[0125] Step S220, sieving the ball-milled raw material to remove iron, and spray drying to obtain powder;

[0126] Step S230, pressing the powder into a green body, drying the green body, and spraying water on the surface of the dried green body;

[0127] Step S240, applying a base glaze and a top glaze to the green body after water spraying, and firing the glazed green body in a kiln at an ambient temperature of 1130° C. to 1200° C. to obtain a light-transmitting ceramic tile;

[0128] Among them, the ring temperature is inversely proportional to the amount of low-temperature melt added.

[0129] Specifically, the raw materials of each part of the green body are mixed together, and water and additives are added for wet ball milling; during ball milling, the fineness is finer, the transparency is better, and the firing range is wider. The laser particle size analysis of the green body fineness in the present invention is as follows Figure 2 As shown. The ball-milled raw materials are screened to remove iron and spray-dried to obtain powder; the evenly mixed powder is sent to the press to be pressed into a green body; after the green body is dried, water slurry is sprayed on the surface of the ceramic tile green body; after water spraying, the brick green body is coated with base glaze and surface glaze; the brick green body is fired in a roller kiln, and the ceramic tile firing kiln with an ambient temperature of 1130℃ to 1200℃ can adapt. The adaptation method is to adjust the ratio of potassium feldspar to low-temperature frit in the green body sintering material. As the ambient temperature increases, the frit ratio increases; as the ambient temperature decreases, the frit ratio increases. That is, keeping the total amount of potassium feldspar and low-temperature frit unchanged and increasing the amount of low-temperature frit used can reduce the firing temperature; reducing the amount of low-temperature frit used can increase the firing temperature. The combination of the two can increase or decrease the green body sintering temperature within a certain range, while the green body transmittance is not affected.

[0130] In a specific embodiment, the raw materials are mixed in proportion, and the components by mass ratio are: 35wt% kaolin, 21wt% strontium carbonate, 10% strontium feldspar, 5wt% quartz, 17wt% potassium feldspar, 12wt% glass powder, and 0.2% sodium carboxymethyl cellulose and 0.8% sodium tripolyphosphate are added. The raw materials are wet-milled and the fineness is controlled to be a particle size D50≤3μm; the ball-milled slurry is sieved to remove iron, and the slurry is spray-dried to obtain a powder; the powder is sent to a press to be pressed and formed, and the formed dry blank is dried in a drying kiln at 150°C, and then inkjet printed; the printed blank enters the glaze line, and the bottom glaze and the top glaze are applied on it, and then it enters the kiln for firing, the ambient temperature is 1145°C, the firing cycle is 42min, and the light transmission effect after firing is as follows Figure 3 The water absorption of the product after firing is less than 0.1%, which meets the requirements of Appendix G of GBT 4100-2015 Ceramic Tiles.

[0131] The embodiments of the present application broaden the firing range of the light-transmitting ceramic tile body and reduce the possibility of deformation of the tile under high temperature; high-temperature over-firing does not cause bulging or foaming, and has good light transmittance, such as Figure 3 shown.

[0132] The embodiment of the present application also provides a light-transmitting ceramic tile, which is prepared by the light-transmitting ceramic tile preparation method of the strontium aluminum silicon system as described above.

[0133] The present invention provides a method for preparing a light-transmitting ceramic tile of a strontium aluminum silicon system and a light-transmitting ceramic tile. The method for preparing a light-transmitting ceramic tile of a strontium aluminum silicon system comprises: selecting a target raw material formula in a pre-constructed raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared; preparing the light-transmitting ceramic tile according to the target raw material formula; wherein the raw material formula table comprises several raw material formulas, and the raw materials in each raw material formula all comprise: kaolin, strontium carbonate, potassium feldspar, low-temperature frit, strontium feldspar and / or quartz, and the weight percentage of kaolin in each raw material formula is different. During the calcination process, the kaolin in the present invention forms strontium feldspar with strontium carbonate, which has a refractive index very close to that of calcium feldspar, and strontium feldspar can form strontium cryolite with potassium sodium feldspar at high temperature, which has a refractive index closer to that of quartz. In this way, mullite no longer exists in the ceramic tile blank, thereby improving the light transmittance of the blank.

[0134] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a strontium aluminum silicon system light-transmitting ceramic tile, characterized in that: The method comprises: Selecting a target raw material formula from a pre-constructed raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared; preparing light-transmitting ceramic tiles according to the target raw material formula; The raw material formula table includes several raw material formulas, and the raw materials in each raw material formula include: kaolin, strontium carbonate, potassium feldspar, low-temperature frit, strontium feldspar and / or quartz, and the weight percentage of kaolin in each raw material formula is different.

2. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 1, characterized in that: The total weight percentage of potassium feldspar and low-temperature melting block in each raw material formula is 25-35%.

3. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 1, characterized in that: The chemical components of the low temperature frit include, by weight percentage: SiO2 70-72%, Al2O3 1-3%, Fe2O3 0-0.2%, TiO2 0-0.05%, CaO 5-10%, MgO 3-5%, K2O 0-1.5%, Na2O 8-16%, and the rest is loss on ignition; Alternatively, the chemical components of the low-temperature frit include, by weight percentage: SiO2 50-60%, Al2O3 2-3%, Fe2O3 0-0.2%, TiO2 0-0.05%, CaO 0-0.5%, MgO 0-0.5%, SrO 8-12%, K2O 0-5%, Na2O 8-16%, and the rest is loss on ignition; Alternatively, the chemical components of the low-temperature frit include, by weight percentage: SiO2 50~60%, Al2O3 2~3%, Fe2O3 0~0.2%, TiO2 0~0.05%, CaO 0~0.5%, MgO 0~0.5%, SrO 8~12%, K2O 0~5%, Na2O 8~16%, MoO3 0~2%, and the rest is loss on ignition.

4. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 1, characterized in that: The preparation steps of the strontium feldspar include: Kaolin, strontium carbonate and potassium feldspar are prepared according to a predetermined raw material formula, and the sintering temperature is 1450℃~1500℃.

5. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 1, characterized in that: The chemical components of the strontium feldspar include, by weight percentage: SiO2 26~31%, Al2O3 20~21%, Fe2O3 0.15~0.25%, TiO2 0~0.05%, CaO0~0.2%, MgO 0~0.2%, SrO 30~35%, K2O 0~1.4%, Na2O 0~0.5%, and the rest is loss on ignition.

6. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 1, characterized in that: The raw material formula in the raw material formula table includes, by weight percentage: Kaolin 20%, strontium carbonate 11-13%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 32-44%; Kaolin 25%, strontium carbonate 14-16%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 24-36%; Kaolin 30%, strontium carbonate 17-19%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 16-28%; Kaolin 35%, strontium carbonate 20-22%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 8-20%; Kaolin 40%, strontium carbonate 23-25%, potassium feldspar + low-temperature frit 25-35%, strontium feldspar and / or quartz 0-12%; Kaolin 45%, strontium carbonate 26-28%, potassium feldspar + low-temperature frit 20-30%, strontium feldspar and / or quartz 0-9%.

7. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 1, characterized in that: Before selecting a target raw material formula in a pre-built raw material formula table according to the specifications of the light-transmitting ceramic tile to be prepared, the following steps are also included: Establish the correspondence between specifications and the weight percentage of kaolin.

8. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 7, characterized in that: According to the specifications of the light-transmitting ceramic tile to be prepared, a target raw material formula is selected from a pre-constructed raw material formula table, including: Find the corresponding relationship according to the specifications of the light-transmitting ceramic tile to be prepared, and obtain the weight percentage of the target kaolin; Select the target raw material formula corresponding to the weight percentage of the target kaolin in the pre-constructed raw material formula table.

9. The method for preparing a strontium aluminum silicon system light-transmitting ceramic tile according to claim 1, characterized in that: The method of preparing a light-transmitting ceramic tile according to the target raw material formula comprises: Mix the raw materials according to the target raw material formula, add water and additives to perform wet ball milling; The ball-milled raw material is sieved to remove iron and spray-dried to obtain a powder; Pressing the powder into a green body, drying the green body, and spraying water on the surface of the dried green body; Applying base glaze and top glaze to the green body after water spraying, and firing the glazed green body in a kiln at an ambient temperature of 1130°C to 1200°C to obtain a light-transmitting ceramic tile; Among them, the ring temperature is inversely proportional to the amount of low-temperature melt added.

10. A light-transmitting ceramic tile, characterized in that: The light-transmitting ceramic tile is prepared by the method for preparing a light-transmitting ceramic tile of a strontium-aluminum-silicon system as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Bone-china exquisite glaze and method for fabricating bone-china exquisite products by using bone-china exquisite glaze

    CN104030732A

  • High-whiteness transparent marble tile blank material, and preparation method thereof

    CN110498675A

  • High-whiteness and high-strength light-transmitting ceramic tile and preparation method thereof

    CN112794707A

  • Rock plate and preparation method thereof

    CN113845357A

  • Light-transmitting ceramic plate with glass refractive index and preparation method thereof

    CN116854457A